2015
DOI: 10.1037/pas0000103
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of DSM-5 section II personality disorder constructs using the MMPI-2-RF in clinical and forensic samples.

Abstract: In the current study, we evaluated the associations between the Minnesota Multiphasic Personality Inventory-2 Restructured Form (MMPI-2-RF; Ben-Porath & Tellegen, 2008) scale scores and the Diagnostic and Statistical Manual of Mental Disorders (5th ed.; DSM-5; American Psychiatric Association, 2013) Section II personality disorder (PD) criterion counts in inpatient and forensic psychiatric samples from The Netherlands using structured clinical interviews to operationalize PDs. The inpatient psychiatric sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
33
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 50 publications
11
33
1
Order By: Relevance
“…Notably, this finding is also similar to previous research on the ICD‐11 trait model (e.g., Carnovale et al, 2020; Sellbom et al, 2020) that found varying levels of discriminant validity for these domains as well. Specific to the MMPI‐2‐RF, previous research on the PSY‐5 scales has also suggested that the Aggressiveness and Disconstraint scales may bifurcate differently under the higher‐order externalizing domain (Anderson et al, 2013, 2015). More specifically, PSY‐5 Disconstraint appears to capture elements of both Disinhibition and Dissociality, whereas Aggressiveness is more specific to certain facets of Dissociality (Anderson et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, this finding is also similar to previous research on the ICD‐11 trait model (e.g., Carnovale et al, 2020; Sellbom et al, 2020) that found varying levels of discriminant validity for these domains as well. Specific to the MMPI‐2‐RF, previous research on the PSY‐5 scales has also suggested that the Aggressiveness and Disconstraint scales may bifurcate differently under the higher‐order externalizing domain (Anderson et al, 2013, 2015). More specifically, PSY‐5 Disconstraint appears to capture elements of both Disinhibition and Dissociality, whereas Aggressiveness is more specific to certain facets of Dissociality (Anderson et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In other words, it is more likely that a situation will drive a subject to exhibit fake-good behaviors (e.g., during personnel selection or qualifying examinations) than fake-bad behaviors. Regarding the measure used, we chose the Minnesota Multiphasic Personality Inventory-2-Restructured Form (MMPI-2-RF; Ben-Porath and Tellegen, 2008 ), as it has been extensively used in clinical (see, e.g., Anderson et al, 2015 ) and selection settings (see, e.g., Tarescavage et al, 2015 ), but not yet used in latency studies. Furthermore, to the best of our knowledge, no prior study has addressed RL and MMPI scores under time pressure conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Right prefrontal and bilateral medial prefrontal pathology may be linked to emotional regulation difficulties or cognitive deficits in attribution or coping while the anterior insular is linked to empathy. A recent systematic review showed a link between narcissism and aggression and violence in both nonclinical and clinical samples (Lambe, Hamilton‐Giachritsis, Garner, & Walker, ). Similarly, a meta‐analysis support the association of narcissism with aggression in response to provocation, especially in those with high entitlement or vulnerable narcissism features (Rasmussen, ). The negative interpersonal impact of NPD individuals on others has recently been supported by empirical studies (Day, Bourke, Townsend, & Grenyer, 2019) and led to a proliferation of self‐help books for those involved in romantic (Behary, ; Malkin, 2015; McBride, ) parent–child (Brown, ; McBride, ) and work relationships (DuBrin, ; Eddy & DiStefano, ; Malkin, ) with NPD individuals. Research on test profile configurations (e.g., MMPI‐2‐RF) can assist the self‐report assessment of NPD (e.g., Anderson et al, ; Sellbom, Smid, De Saeger, Smit, & Kamphuis, ; Sellbom & Smith, ).…”
Section: New and Emerging Developmentsmentioning
confidence: 99%
“…• The negative interpersonal impact of NPD individuals on others has recently been supported by empirical studies (Day, Bourke, Townsend, & Grenyer, 2019) and led to a proliferation of self-help books for those involved in romantic (Behary, 2013;Malkin, 2015;McBride, 2015) parent-child (Brown, 2008;McBride, 2008) and work relationships (DuBrin, 2012;Eddy & DiStefano, 2015;Malkin, 2015) with NPD individuals. • Research on test profile configurations (e.g., MMPI-2-RF) can assist the self-report assessment of NPD (e.g., Anderson et al, 2015;Sellbom, Smid, De Saeger, Smit, & Kamphuis, 2014;Sellbom & Smith, 2017).…”
Section: New and Emerging Developmentsmentioning
confidence: 99%